Improving Students Reading Comprehension Through Mind Mapping Technique in Narrative Text - Elwin Piarawan Zebua (LP. Ma'arif Janggan Magetan, 2022)
Reading is a process that is carried out and used by the reader to get the message from the writer. Reading improves the ability to understand words and improve thinking skills, increase creativity and also gets acquainted with new ideas. Based on the observation in SMK N 1 Gunungsitoli Barat especially class XI IPA 2, the researcher found that the students were difficult to get some information of the text and the students unable to understand the meaning of the text. This research was conducted to improve students reading comprehension through Mind Mapping technique in narrative text at the eleventh grade of SMK N 1 Gunungsitoli Barat in 2021/2022. Through Classroom Action Research (CAR, the research was conducted in two cycles. The result of the research revealed the Mind Mapping technique improves students’ ability in Reading Comprehension. Hence, the English teacher of SMK N 1 Gunungsitoli Barat were suggested to use Mind Mapping technique to improve the students ability in reading comprehension because the strategy guides the students’ ideas and also helped in finding out the ideas in reading.